Silver Nanoparticles - Fabrication, Characterization and Applications 2018
DOI: 10.5772/intechopen.76947
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Operational Factors and Characterization Imperative to the Synthesis of Silver Nanoparticles

Abstract: The synthesis and application of silver nanoparticles are increasingly becoming attractive. Hence, a critical examination of the various factors needed for the synthesis of silver nanoparticles as well as the characterization is imperative. In light of this, we addressed in this chapter, the nitty-gritty on the operational parameters (factors) and characterization relevant to synthesis of silver nanoparticle. The following characterization protocols were discussed in the context of silver nanoparticle synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 78 publications
6
39
0
1
Order By: Relevance
“…Figure 3A revealed that the maximum absorption was observed at 430 nm which was due to the AgNPs SPR band. The SPR is as a result of the free electron arising from the conduction and valence bands lying close to each other in metal nanoparticles ( Anandalakshmi, Venugobal & Ramasamy, 2016 ; Dada et al, 2018 ). This SPR peak gives a convenient spectroscopic signature for the formation of AgNP and a clue on the spherical shape of AgNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3A revealed that the maximum absorption was observed at 430 nm which was due to the AgNPs SPR band. The SPR is as a result of the free electron arising from the conduction and valence bands lying close to each other in metal nanoparticles ( Anandalakshmi, Venugobal & Ramasamy, 2016 ; Dada et al, 2018 ). This SPR peak gives a convenient spectroscopic signature for the formation of AgNP and a clue on the spherical shape of AgNP.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption of energy in the form of ultraviolet or visible light is by molecules containing π-electrons or non-bonding electrons ( n -electrons) to excite these electrons to higher anti-bonding molecular orbitals. The length of wave depends on the excitation of the electrons, the more easily excited the electrons, the longer the wavelength of light it can absorb ( Dada et al, 2018 ). Oscillation of electron at the surface of AgNPs brought about the SPR resulting from the change of color from green to yellow and finally brown.…”
Section: Characterizationmentioning
confidence: 99%
“…The form products formed are stable, well dispersed with limited aggregation and afford better size control with no sludge generation. Recently, various plant parts such as leaves, stem bark, roots as well as their extracts are now being used to synthesize nanoparticles because they are greener and can also serve as stabilizing and reducing agents for the synthesis (Dada et al., 2018a,b; Song and Kim, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…3(a) revealed that the maximum absorption was observed at 430 nm which was due to the AgNPs surface plasmon resonance (SPR) band. The surface plasmon resonance is as a result of the free electron arising from the conduction and valence bands lying close to each other in metal nanoparticles (Anandalakshmi et al, 2016;Dada et al, 2018). This SPR peak gives a convenient spectroscopic signature for the formation of silver nanoparticle (AgNPs) and a clue on the spherical shape of silver nanoparticle.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption of energy in the form of ultraviolet or visible light is by molecules containing πelectrons or non-bonding electrons (n-electrons) to excite these electrons to higher anti-bonding molecular orbitals. The length of wave depends on the excitation of the electrons, the more easily excited the electrons, the longer the wavelength of light it can absorb (Dada et al, 2018).…”
Section: Characterization Uv-vis Spectroscopic Studymentioning
confidence: 99%